Iron-carbon composite flux for strengthening the separation of copper matte and slag in copper smelting process

CN117344151BActive Publication Date: 2026-10-30FUZHOU UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311331439.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-16
Publication Date
2026-10-30
Estimated Expiration
2043-10-16

AI Technical Summary

Technical Problem

对此,工业上常采用直接投放铁棒或者煤炭等还原剂来破坏该“横膈膜”,然而铁棒密度大,反应过程迅速沉底至冰铜层,利用率低、消除“横膈膜”的效率也较低;而煤炭还原剂密度过小,无法达到冰铜-熔渣界面层并直接参与“横膈膜”处四氧化三铁的还原消除

Benefits of technology

本发明采用铁、碳为原料,煤沥青或磷生铁为粘结剂,通过复合洗炉剂特定密度及形状的联合设计,即在粘结剂的作用下将金属铁棒固定于碳质还原剂内,形成螺钉型、棒球棒型、伞型或船型复合洗炉剂,并控制复合洗炉剂的表观密度为3.7~5.3 g/cm3,从而使其可靶向停留于铜锍-熔渣的界面层处,实现对“横膈膜”内四氧化三铁的定点还原清除,促进熔渣内冰铜液滴的沉降聚合及冰铜-熔渣的分层;另外,还原反应中会产生气体,通过产气搅拌可强化对渣层和冰铜层之间四氧化三铁“横膈膜”的物理破除作用,进一步促进铜渣中铜锍的沉降。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The application discloses a kind of iron-carbon composite stove washing agent for strengthening copper smelting process copper-slag stratification, which is with metal iron bar, carbonaceous material as raw material, carbonaceous material is first pressed into cake, sheet or semisphere, then metal iron bar and shaped carbonaceous material are bonded into specific shape by using binder to be made;Its apparent density is 3.7~5.3 g / cm 3 When the obtained iron-carbon composite stove washing agent is added to copper smelting smelting furnace, the composite stove washing agent can target and stay in the "diaphragm" layer containing magnetite at the copper matte-slag interface, accurately reduce the magnetite particles at the "diaphragm", and strengthen the settlement and stratification of copper matte droplets in the slag, which has good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of metallurgy, specifically relating to an iron-carbon composite furnace cleaning agent that enhances the stratification of matte and slag during copper smelting. Background Technology

[0002] Modern copper smelting employs oxygen-enriched intensified smelting, inevitably generating a large amount of high-melting-point iron(III) oxide (Fe3O4) solid particles. These particles accumulate between the bottom copper matte pool and the upper slag layer, forming a "diaphragm" that hinders the settling and separation of copper matte droplets within the slag, resulting in high copper content in the slag and insufficient copper yield. Industrially, this is often addressed by directly adding reducing agents such as iron rods or coal to break down this "diaphragm." However, iron rods, with their high density, quickly sink to the bottom of the matte layer during the reaction, leading to low utilization and inefficient elimination of the "diaphragm." Coal, on the other hand, has too low a density to reach the matte-slag interface and directly participate in the reduction and elimination of Fe3O4 at the "diaphragm." This invention, through the composite of iron and carbon, combined with the combined control of density and shape, enables the resulting iron-carbon composite furnace cleaning agent to target and remain at the diaphragm, precisely reducing the Fe3O4 particles there and enhancing the settling and stratification of matte droplets within the slag. Summary of the Invention

[0003] To address the aforementioned problems, this invention provides an iron-carbon composite furnace cleaning agent that enhances the stratification of matte and slag during copper smelting.

[0004] To achieve the above objectives, the present invention adopts the following technical solution: A composite iron-carbon furnace cleaning agent for enhancing matte-slag stratification during copper smelting is disclosed. It is made from metal iron rods and carbonaceous materials. The carbonaceous materials are first pressed into cakes, sheets, or hemispheres, and then a binder is used to bond the metal iron rods and the shaped carbonaceous materials into a specific shape. This allows the composite furnace cleaning agent to be targeted and retained on the diaphragm. The apparent density of the resulting composite iron-carbon furnace cleaning agent is 3.7~5.3 g / cm³. 3 .

[0005] Furthermore, the mass percentage ratio of the carbon-containing material to the metal iron rod is (6~4):(4~6).

[0006] Furthermore, the aspect ratio of the metal rod is (10~1):1.

[0007] Furthermore, the carbon-containing substance is any one or more of petroleum coke, pulverized coal, and pitch coke.

[0008] Furthermore, the carbonaceous material must be calcined and crushed before use; the particle size after crushing is divided into any one of coarse coke (12~6 mm), medium coke (6~3 mm), fine coke (3~1 mm), and powdered coke (less than 0.075 mm).

[0009] Furthermore, the binder is coal tar pitch or pig iron phosphate.

[0010] Furthermore, the amount of the binder added is 5% to 15% of the total mass of the metal iron rod and carbonaceous material used.

[0011] Furthermore, the specific shape includes screw-shaped, baseball bat-shaped, umbrella-shaped, or boat-shaped. Specifically, when the iron-carbon composite furnace cleaning agent is screw-shaped, its upper "nut" is a disc-shaped carbonaceous material, and its lower "screw" is a metal iron rod. The outer diameter of the "nut" is approximately 80 mm, and the outer diameter of the "screw" is approximately 10 mm. When the iron-carbon composite furnace cleaning agent is baseball bat-shaped, its "inner core" is a metal iron rod, and its "outer" is formed by a sheet-like carbonaceous material wrapping around the "inner core." The maximum diameter of its overall shape is 50 mm, and its length is 100 mm. When the iron-carbon composite furnace cleaning agent is umbrella-shaped, its "umbrella surface" is a hemispherical carbonaceous material, and its "umbrella ribs" are metal iron rods. The outer diameter of the "umbrella surface" is 50 mm, and the length of the "umbrella ribs" is 50-100 mm. When the iron-carbon composite furnace cleaning agent is boat-shaped, its upper "staff" is a metal iron rod, and its lower "hull" is a hemispherical carbonaceous material. The diameter of the "staff" is 10 mm, and its length is 50-100 mm. The diameter of the "hull" is 50 mm.

[0012] Furthermore, the amount of the iron-carbon composite furnace cleaning agent used in the copper smelting process is 0.5% to 4% of the slag mass, which can reduce the copper content in the slag to below 0.5%.

[0013] The significant advantages of this invention are: This invention uses iron and carbon as raw materials, and coal tar pitch or pig iron phosphate as a binder. Through the combined design of specific density and shape of the composite furnace cleaning agent, a metal iron rod is fixed within a carbonaceous reducing agent under the action of the binder, forming a screw-shaped, baseball bat-shaped, umbrella-shaped, or boat-shaped composite furnace cleaning agent. The apparent density of the composite furnace cleaning agent is controlled to be 3.7~5.3 g / cm³. 3 This allows it to target and remain at the interface layer between copper matte and slag, achieving targeted reduction and removal of iron(III) oxide within the "diaphragm," promoting the sedimentation and polymerization of matte droplets in the slag and the stratification of matte and slag. In addition, the reduction reaction generates gas, and the gas-generating stirring can enhance the physical removal of the iron(III) oxide "diaphragm" between the slag layer and the matte layer, further promoting the sedimentation of copper matte in the copper slag. Attached Figure Description

[0014] Figure 1 This is a schematic diagram of the screw-type composite furnace cleaning agent obtained in Example 1.

[0015] Figure 2 This is a schematic diagram of the structure of the baseball bat-shaped composite furnace cleaning agent obtained in Example 2.

[0016] Figure 3 This is a schematic diagram of the structure of the umbrella-shaped composite furnace cleaning agent obtained in Example 3.

[0017] Figure 4 This is a schematic diagram of the structure of the ship-shaped composite furnace cleaning agent obtained in Example 4. Detailed Implementation

[0018] The following are specific implementation examples based on the technical solution of this invention. The invention can be better understood through these embodiments and in conjunction with the accompanying drawings. It should be noted that this invention is not limited to the following embodiments. Any non-substantial modifications or alterations to the form or content of this invention made by those skilled in the art based on the principles of this invention are within the scope of protection of this invention.

[0019] Example 1: Using petroleum coke as the carbonaceous material and 10 mm diameter iron rods as the raw material, and pig iron as the binder, the raw materials are prepared at a mass ratio of 6:4 (carbonaceous material to iron rods) and 15% (binder) of the total mass of iron rods and carbonaceous material. The petroleum coke is pre-calcined at 1300℃ and then crushed into coarse coke particles of 12-6 mm. The crushed petroleum coke is then poured into a mold and pressed into a cake shape. Molten pig iron is then cast into the pre-reserved slots in the petroleum coke cake, and the iron rods are embedded in the slots. After cooling, a screw-type composite furnace cleaning agent is produced, with petroleum coke as the "nut" and the iron rod as the "screw." The "nut" has a diameter of approximately 80 mm and a height of 10 mm, and the "screw" has a diameter of 10 mm and a height of 50 mm. The apparent density, measured by a true density meter, is 3.7 g / cm³. 3 .

[0020] A copper smelting furnace contained 120 tons of copper slag in its molten pool. The slag contained 2% copper, and the slag temperature was 1250 ℃. Measurement sampling revealed a 20 mm thick iron tetroxide (Fe3O4) "diaphragm" layer at the matte-slag interface. After adding 0.6 tons of a prepared screw-shaped composite furnace cleaning agent and reacting for 0.5 hours, the "diaphragm" thickness decreased to 5 mm, and the copper content in the slag decreased to 0.6%.

[0021] Example 2: Using pulverized coal as the carbonaceous material and 10 mm diameter metal rods as the raw material, and coal tar pitch as the binder, the raw materials are prepared at a mass ratio of 5:5 (carbonaceous material to metal rods) and 10% (binder) of the total mass of metal rods and carbonaceous material. The pulverized coal is pre-calcined at 1300℃ and then crushed into coarse coke with a particle size of 12-6 mm. The crushed pulverized coal is then mixed with coal tar pitch and spread into sheets. The metal rods are placed in the center of the sheets, and the sheets are then rolled up to wrap the metal rods, creating a baseball-shaped composite furnace cleaning agent with the metal rods as the "inner core" and pulverized coal as the "outer layer." The overall dimensions are: maximum diameter 50 mm, length 100 mm, and the central metal rod has a diameter of 10 mm and a length of 120 mm. The apparent density, measured by a true density meter, is 5.3 g / cm³. 3 .

[0022] A copper smelting furnace contained 100 tons of copper slag in its molten pool. The slag contained 1.8% copper, and the slag temperature was 1300 ℃. Measurement sampling revealed a 18 mm thick iron tetroxide (Fe3O4) "diaphragm" layer at the matte-slag interface. After adding 4 tons of a prepared baseball bat-shaped composite furnace cleaning agent and reacting for 1 hour, the "diaphragm" thickness decreased to 3 mm, and the copper content in the slag decreased to 0.4%.

[0023] Example 3: Using pitch coke as the carbonaceous material and 10 mm diameter iron rods as the raw material, and pig iron as the binder, the materials are prepared at a mass ratio of 6:4 (carbonaceous material to iron rods) and 5% (binder) of the total mass of iron rods and carbonaceous material. The pitch coke is pre-calcined at 1300℃ and then crushed into medium coke particles of 6-3 mm. The crushed pitch coke is then poured into a mold and pressed into a hemispherical shape. Molten pig iron is cast into the pre-reserved slots in the pitch coke blocks, and the iron rods are then embedded in the slots. After cooling, an umbrella-shaped composite furnace cleaning agent is produced, with pitch coke as the "umbrella surface" and iron rods as the "umbrella ribs." The "umbrella surface" has an outer diameter of 50 mm and a length of 10 mm, and the "umbrella ribs" have a diameter of 10 mm and a length of 100 mm. Its apparent density, measured by a true density meter, is 5.0 g / cm³. 3 .

[0024] A copper smelting furnace contained 110 tons of copper slag in its molten pool, with a copper content of 2.5%. The slag temperature was 1280 ℃. Measurement sampling revealed a 25 mm thick iron tetroxide (Fe3O4) diaphragm layer at the matte-slag interface. After adding 2 tons of a prepared umbrella-shaped composite furnace cleaning agent and reacting for 1.5 hours, the diaphragm thickness decreased to 5 mm, and the copper content in the slag decreased to 0.5%.

[0025] Example 4: Using pitch coke as the carbonaceous material and 15 mm diameter iron rods as the raw material, and pig iron as the binder, the mixture is prepared with a carbonaceous material to iron rod mass ratio of 4:6 and the binder mass being 15% of the total mass of the iron rods and carbonaceous material. The pitch coke is pre-calcined at 1300℃ and then crushed into fine coke particles of 3-1 mm. The crushed pitch coke is then poured into a mold and pressed into a hemispherical shape. Molten pig iron is cast into the pre-reserved slots in the pitch coke blocks, and the iron rods are then embedded in the slots. After cooling, a boat-shaped composite furnace cleaning agent is produced, with pitch coke as the "hull" and iron rods as the "stirrups." The "hull" is approximately 100 mm long and 20 mm high, and the "stirrups" are 15 mm in diameter and 50 mm high. Its apparent density, measured by a true density meter, is 4.5 g / cm³. 3 .

[0026] A copper smelting furnace contained 110 tons of copper slag in its molten pool, with a copper content of 2.0% and a slag temperature of 1260 ℃. Measurement sampling revealed a 20 mm thick iron tetroxide (Fe3O4) "diaphragm" layer at the matte-slag interface. After adding 3 tons of a pre-prepared ship-shaped composite furnace cleaning agent and reacting for 1 hour, the "diaphragm" thickness decreased to 3 mm, and the copper content in the slag decreased to 0.4%.

[0027] Comparative Example 1: Using petroleum coke as the carbonaceous material and 10 mm diameter iron blocks as the raw material, and pig iron as the binder, the raw materials are prepared at a mass ratio of 6:4 (carbonaceous material to iron blocks) and 15% (binder) of the total mass of iron blocks and carbonaceous material. The petroleum coke is pre-calcined at 1300℃ and then crushed into coarse coke particles of 12-6 mm. The crushed petroleum coke is then poured into a mold and pressed into rod shapes. Pig iron is then cast into pre-reserved slots in the iron blocks, and the petroleum coke rods are embedded in the slots. After cooling, a screw-type composite furnace cleaning agent is produced, with the iron blocks as "nuts" and the petroleum coke as "screws." The "nuts" are approximately 80 mm in diameter and 0.78 mm high, and the "screws" are approximately 10 mm in diameter and 50 mm high. The apparent density, measured by a true density meter, is 3.7 g / cm³. 3 .

[0028] A copper smelting furnace contained 120 tons of copper slag in its molten pool, with a copper content of 2%. The slag temperature was 1250 ℃. Measurement sampling revealed a 20 mm thick iron tetroxide (Fe3O4) diaphragm layer at the matte-slag interface. After adding 0.6 tons of a prepared screw-type composite furnace cleaning agent and reacting for 0.5 hours, the diaphragm thickness decreased to 18 mm, and the copper content in the slag was reduced to 1.5%.

[0029] Comparative Example 2: Using petroleum coke as the carbonaceous material and 10 mm diameter iron rods as the raw material, and pig iron as the binder, the raw materials are prepared at a mass ratio of 6:4 (carbonaceous material to iron rods) and 15% (binder) of the total mass of iron rods and carbonaceous material. The petroleum coke is directly crushed into coarse coke particles of 12-6 mm. The crushed petroleum coke is then poured into a mold and pressed into a cake shape. Molten pig iron is then cast into pre-reserved slots in the petroleum coke cake, and the iron rods are embedded in the slots. After cooling, a screw-type composite furnace cleaning agent is produced, with petroleum coke as the "nut" and the iron rods as the "screws." The "nut" has a diameter of approximately 80 mm and a height of 10 mm, and the "screw" has a diameter of 10 mm and a height of 50 mm. Its apparent density, measured by a true density meter, is 3.7 g / cm³. 3 .

[0030] A copper smelting furnace contained 120 tons of copper slag in its molten pool, with a copper content of 2%. The slag temperature was 1250 ℃. Measurement sampling revealed a 20 mm thick iron tetroxide (Fe3O4) diaphragm layer at the matte-slag interface. After adding 0.6 tons of a prepared screw-shaped composite furnace cleaning agent and reacting for 0.5 hours, the diaphragm thickness decreased to 9 mm, and the copper content in the slag dropped to only 1%.

[0031] Comparative Example 3: Using petroleum coke as the carbonaceous material and 10 mm diameter iron rods as the raw material, and pig iron as the binder, the raw materials are prepared at a mass ratio of 6:4 (carbonaceous material to iron rods) and 15% (binder) of the total mass of iron rods and carbonaceous material. The petroleum coke is pre-calcined at 1300℃ and then crushed into particles of 15-12 mm. The crushed petroleum coke is then poured into a mold and pressed into a cake shape. Molten pig iron is then cast into pre-reserved slots in the petroleum coke cake, and the iron rods are embedded in the slots. After cooling, a screw-type composite furnace cleaning agent is produced, with petroleum coke as the "nut" and the iron rod as the "screw." The "nut" has a diameter of approximately 80 mm and a height of 10 mm, and the "screw" has a diameter of 10 mm and a height of 50 mm. The apparent density, measured by a true density meter, is 3.7 g / cm³. 3 .

[0032] A copper smelting furnace contained 120 tons of copper slag in its molten pool, with a copper content of 2%. The slag temperature was 1250 ℃. Measurement sampling revealed a 20 mm thick iron tetroxide (Fe3O4) diaphragm layer at the matte-slag interface. After adding 0.6 tons of a prepared screw-type composite furnace cleaning agent and reacting for 0.5 hours, the diaphragm thickness remained at 20 mm, and the copper content in the slag decreased to 0.8%.

[0033] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made within the scope of the claims of the present invention should be included in the scope of the present invention.

Claims

1. A carbon-iron composite furnace cleaning agent for enhancing matte-slag stratification during copper smelting, characterized in that, Using petroleum coke as the carbonaceous material and 10mm diameter iron rods as the raw material, and pig iron as the binder, the raw materials are prepared at a mass ratio of 6:4 (carbonaceous material to iron rods) and 15% (binder) of the total mass of iron rods and carbonaceous material. The petroleum coke is pre-calcined at 1300℃ and then crushed into coarse coke particles of 12-6mm. The crushed petroleum coke is then poured into a mold and pressed into a cake shape. Molten pig iron is then cast into the pre-reserved slots in the petroleum coke cake, and the iron rods are embedded in the slots. After cooling, a screw-type composite furnace cleaning agent is produced, with petroleum coke as the "nut" and the iron rods as the "screws." The "nut" has a diameter of 80mm and a height of 10mm, and the "screw" has a diameter of 10mm and a height of 50mm. The apparent density, measured by a true density meter, is 3.7g / cm³. 3 .

Citation Information

Patent Citations

  • Method for efficiently eliminating ferroferric oxide in copper smelting slag

    CN115369259A